Interactive Learning Media Development Articulate Storyline to Improve Science Literacy Capabilities of Junior High School Students - Adela Kristiani; Diah Wahyuni; Sri Wahyuni (Universitas Lambung Mangkurat, 2022)
The purpose of the research was to determine the validity, practicality and effectiveness of interactive learning media based on Articulate Storyline on Global Warming Materials to improve the science literacy skills of junior high school students. The type of research uses development research with the model ADDIE. This research was conducted on class VII B students at one of the schools in the city of Probolinggo. This study used data collection techniques and instruments, including validation sheets, observation sheets of learning outcomes, tests, interviews and documentation. The results showed that interactive learning media based on Articulate Storyline is very valid with a percentage of 94.25%, very practical with a percentage of 92%, quite effective with an N-gain of 0.52 and a percentage of student response of 85%. So, interactive learning media based on Articulate Storyline on Global Warming Materials can be very feasible to use in science learning to improve the science literacy skills of junior high school students.